Emotional and Artificial Intelligence: Narrative of Human and Machine Relation - Hossain, Akhter (Transactions on Engineering and Computing Sciences, 2025)
Emotional intelligence (EI) includes social skills, motivation, self-awareness, empathy, and emotional regulation. These qualities are essential for successful personal and professional lives, strong relationships, and complex social interactions. The field of computer science known as artificial intelligence (AI) creates algorithms and systems that carry out operations like observation, reasoning, learning, and decision-making that normally calls for human intelligence. The replication of human intelligence in computers that are built to comprehend, learn, and make decisions is known as AI. It can improve overall efficiency, fortify the decision-making process, and aid in the more efficient delivery of services. AI has advanced significantly over the last few decades; machines can now comprehend language, analyze voice and visuals, and even defeat chess grandmasters. In order to help therapists adapt their treatments to their patients' emotional needs, AI systems can analyze speech patterns and facial expressions during therapy. A number of exciting research avenues could connect AI with EI. Developing AI systems that can identify emotions and act accordingly is a key area of research. This calls for advancements in robot motion control to provide personified reactions that show comprehension and affection, as well as in natural language processing (NLP) to produce emotionally complex text and voice. Researchers must examine the moral ramifications of AI-driven emotional manipulation and the possibility of bias in emotional detection algorithms in order to develop and implement these technologies in an ethical manner. In several areas, AI may enhance EI. AI will be able to identify and react to emotions in sympathetic and organic ways as AI and emotional intelligence research progresses, facilitating more acceptable and natural human-machine interactions. In order to ensure that AI can comprehend and react to human emotions in an ethical manner, protecting individuality and privacy while avoiding prejudices and possible exploitation, it is imperative that emotional intelligence be taken into account in ethical frameworks for AI. The purpose of this analytical work is to assess the relationship between AI and EI, as well as to describe the potential future effects of human-machine contact and consequences.